Effects of calcium propionate on the fermentation quality and aerobic stability of alfalfa silage - Dong, Zhihao (Asian-Australasian journal of animal sciences, 2017)
OBJECTIVE: To assess the potency of calcium propionate (CAP) used as silage additive, an experiment was carried out to evaluate the effect of CAP on the nitrogen transformation, fermentation quality and aerobic stability of alfalfa silages